2018
DOI: 10.1002/jmri.25955
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Sweep Imaging With Fourier Transform for Evaluation of Cortical Bone in Diabetic Rats

Abstract: 1 Technical Efficacy: Stage 3 J. MAGN. RESON. IMAGING 2018;48:389-397.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The specimens were all placed with the same orientation to ensure an identical ip angle (FA). SWIFT was performed using the following protocol: eld of view (FOV) of 40 × 240 × 40 mm 3 ; matrix of 256 × 256 × 256; 16 spirals; 8192 views; average of 1; resolution of 0.156 × 0.938 × 0.156 mm 3 ; bandwidth of 62 5 kHz; repetition time (TR) of 12.5 ms; FA of 25°; acquisition time of 4.096 ms; and scan time of 27 min 25 s. The proton densityweighted image (PDWI) was obtained according to the following protocol using a conventional fast spin echo method: FOV of 40 × 40 mm 2 ; matrix of 256 × 256; average of 1; resolution of 0.156 × 0.156 mm 2 ; axial slice of 30; slice thickness of 1 mm; bandwidth of 100 kHz; TR of 2000 ms; echo spacing (ESP) of 9.54 ms; echo train length of 4; acquisition time of 2.56 ms; and scan time of 2 min 13 s. These protocols were similar to those described in previous reports [10,11]. The images were analyzed using a software program (ImageJ v. 1.49, National Institutes of Health, Bethesda, MD).…”
Section: Mrimentioning
confidence: 78%
See 1 more Smart Citation
“…The specimens were all placed with the same orientation to ensure an identical ip angle (FA). SWIFT was performed using the following protocol: eld of view (FOV) of 40 × 240 × 40 mm 3 ; matrix of 256 × 256 × 256; 16 spirals; 8192 views; average of 1; resolution of 0.156 × 0.938 × 0.156 mm 3 ; bandwidth of 62 5 kHz; repetition time (TR) of 12.5 ms; FA of 25°; acquisition time of 4.096 ms; and scan time of 27 min 25 s. The proton densityweighted image (PDWI) was obtained according to the following protocol using a conventional fast spin echo method: FOV of 40 × 40 mm 2 ; matrix of 256 × 256; average of 1; resolution of 0.156 × 0.156 mm 2 ; axial slice of 30; slice thickness of 1 mm; bandwidth of 100 kHz; TR of 2000 ms; echo spacing (ESP) of 9.54 ms; echo train length of 4; acquisition time of 2.56 ms; and scan time of 2 min 13 s. These protocols were similar to those described in previous reports [10,11]. The images were analyzed using a software program (ImageJ v. 1.49, National Institutes of Health, Bethesda, MD).…”
Section: Mrimentioning
confidence: 78%
“…Sweep imaging with Fourier transform (SWIFT) is a novel imaging method in magnetic resonance imaging (MRI) that can depict proton signals with very short T 2 relaxation times that cannot be measured by conventional MRI [9]. It has been reported that SWIFT can detect proton signals associated with bone turnover in the cortical bone of postmenopausal osteoporotic and diabetic osteoporotic rats [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The bone metabolism of patients with osteoporosis is abnormal, and their bone loss is aggravated, thus leading to decreased bone strength and increasing their risk of fractures. If patients with T2DM develop osteoporosis, then their risk of disability is increased, thereby adversely affecting their prognosis[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…SWIFT MRI (using a TE ~ 0) could detect changes between diabetic and control male Wistar/ST rats two weeks following streptozotocin (STZ) injections to induce T1D, where changes in BMD were not detectable until week eight ( Minami et al, 2018 ). At two weeks post STZ, mechanical properties including stiffness and energy absorption were significantly compromised and bone formation measured via histomorphometry was suppressed.…”
Section: Bone Water With Age and Diseasementioning
confidence: 99%